2009
DOI: 10.1037/a0015020
|View full text |Cite
|
Sign up to set email alerts
|

Children discover the spectral skeletons in their native language before the amplitude envelopes.

Abstract: Much of speech perception research has focused on brief spectro-temporal properties in the signal, but some studies have shown that adults can recover linguistic form when those properties are absent. In this experiment, seven-year-old English-speaking children demonstrated adult-like abilities to understand speech when only sine waves replicating the three lowest resonances of the vocal tract were presented, but failed to demonstrate comparable abilities when noise bands amplitude-modulated with envelopes der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 44 publications
(52 reference statements)
3
67
2
Order By: Relevance
“…Of course, signals in this second experiment, as well as those in Nittrouer et al ͑2009͒, shared another attribute. In both cases they were constructed entirely of noise.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Of course, signals in this second experiment, as well as those in Nittrouer et al ͑2009͒, shared another attribute. In both cases they were constructed entirely of noise.…”
Section: Discussionmentioning
confidence: 75%
“…In both cases they were constructed entirely of noise. That means that possibly the shift away from weighting formant transitions strongly demonstrated by this experiment and by the poor sentence recognition found in Nittrouer et al ͑2009͒ for noisy stimuli might be attributable to children failing to attend to noise components in speech signals. The current study cannot really separate the contributions made to children's results of broadened bandwidths and noisy signals.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Yet Nittrouer and colleagues (Nittrouer and Lowenstein, 2010;Nittrouer et al, 2009) found that the ability to interpret these NV speech and sine-wave analogs had different developmental time courses. Relative to adults, children aged 3-7 yr had much greater difficulty with NV speech than with sine-wave speech.…”
Section: Introductionmentioning
confidence: 99%
“…The authors interpreted these results as indicating that children rely on dynamic spectral information to a greater extent than do adults and thus have particular difficulty with NV signals that lack such information. Or, to put it another way, children learn initially to focus on spectral information and thus "learn to extract linguistic form from signals that preserve some spectral structure" earlier in development (Nittrouer et al, 2009(Nittrouer et al, , p. 1245. Such results have implications for children hearing speech through cochlear implants, at least if normal-hearing children's performance with NV speech serves as a model for children's performance with an actual implant.…”
Section: Introductionmentioning
confidence: 99%